Integration of STEM-Based E-Modules to Improve Conceptual Understanding and Digital Literacy in the Human Respiratory System - Sri Minarti; Evy Yulianti; Intan Meifilindati (International Forum of Researchers and Lecturers, 2025)
This research is motivated by challenges in biology learning, including the lack of digital literacy assessment in schools and the use of conventional learning methods that tend to make students bored. Impractical printed teaching materials cannot be integrated into the form of videos. This research aims to develop an e-module based on Science, Technology, Engineering, and Mathematics (STEM) to analyze the feasibility, practicality, and effectiveness of e-modules in improving students' understanding of concepts and digital literacy on human respiratory system materials. This research uses the Development Research (R&D) method with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. The research was carried out at SMAN 1 Malinau. The implementation stage used a non-equivalent control group design involving 34 students in the experimental class and the control class. Data collection instruments include validation sheets for media and material experts, practicality questionnaires for teachers and students, and pretest-posttest tests to measure concept understanding and digital literacy. Analysis of effectiveness data using N-gain test and hypothesis test (independent sample t-test for concept understanding and Mann-Whitney for digital literacy). The results of the research based on the validation of media experts and subject matter experts show that the STEM-based e-module is declared